0
$\begingroup$

I wanted to prove that

$$\lim_{x \to \infty} (-x^3 + x^2) = - \infty$$

which is obvious. But when I tried using L'Hôpitals rule, I ran into a wrong answer.

My try was the following:

$$f(x) = -x^3 + x^2 = x^2 (-x + 1) = \frac{-x +1}{x^{-2}}$$

Now take the derivative of the function over and under the fraction:

$$\lim_{x \to \infty} \frac{-x +1}{x^{-2}} = \lim_{x \to \infty} \frac{-1}{-2x^{-3}}$$

But

$$\lim_{x \to \infty} \frac{-1}{-2x^{-3}} = \lim_{x \to \infty} 0.5 x^3 = \infty$$

which now gives the wrong result. What am I overlooking?

$\endgroup$
  • 3
    $\begingroup$ you can't apply L'hospital's rule here $\endgroup$ – haqnatural Aug 7 '17 at 15:12
3
$\begingroup$

You just can't apply L'Hopital rule, since $\frac{-x+1}{x^{-2}}$ is not an indeterminate form as $x\to \infty$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.